Taxonomic revision of ternstroemia (pentaphylacaceae) in Borneo - Suzana Sabran (2019)
Ternstroemia (Pentaphylacaceae) is a pantropical genus of about 100 species, consisting of trees, shrubs and epiphytes. Previous studies merely listed species and sometimes with brief species descriptions of Ternstroemia in separate accounts of the various regions in Borneo. There being no consolidated accounts for Borneo, a taxonomic study of the species of Ternstroemia in Borneo was undertaken. The aims of this study are to identify distinguishing characters, construct a taxonomic key to species, prepare descriptions and update the checklist of Ternstroemia in Borneo. A total of 120 specimens of Ternstroemia species were collected from 19 localities within Sabah and Sarawak from 2013 until 2018. A total of 1312 herbarium specimens of Ternstroemia species from 12 herbaria, i.e. A, BO, BRUN, K, KEP, KNP, L, PNH, SAN, SAR, SING and BORH, were examined. This study is the first comprehensive taxonomic revision of the genus in Borneo based on gross morphology of vegetative and reproductive characters. Detailed descriptions of all the Ternstroemia species including the key to the species and also an updated checklist of Ternstroemia in Borneo was prepared. There is no single morphological character which can be used to delimit any recognised species among the Ternstroemia in Borneo. A combination of vegetative and reproductive morphological characters especially the leaves sizes, textures and shapes and also the flower sizes are useful and more applicable ways to distinguish the 17 species of Ternstroemia in Borneo. From the study, 17 species of Ternstroemia are now recognised in Borneo, including eight species new to science. Sabah and Sarawak has the highest number of species among the geographical areas of Borneo with 17 species, followed by Kalimantan with 13 species and Brunei with 12 species. The number of endemic species of Ternstroemia in Borneo is very high with eleven species (64.7%), namely Ternstroemia beccarii Stapf ex Ridl., T. citnna Rid I., T. hosei Rid I., T. /owii Stapf, r. borneensis S. Suzana & E. Soepadmo, T. pereirae S. Suzana & E. Soepadmo, r. postarii S. Suzana & E. Soepadmo, T. long1folius S. Suzana & E. Soepadmo, T. crass,folium S. Suzana & E. Soepadmo, T. sugaui S. Suzana & E. Soepadmo and r. suleimanae S. Suzana & E. Soepadmo.